2021
DOI: 10.1002/rhc3.12239
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of social vulnerability and proximity to coal‐fired power plants and windmill farms

Abstract: This research examines if there are differences in the social vulnerability of U.S. residents living within a five‐mile radius of a coal‐fired power plant compared to residents living within a five‐mile radius of a windmill farm (N = 5776) for facilities in operation as of April 2020. Two logistic regression models were created with demographic data for 2020 and 2010 to account for the decline of the coal power industry and rise of the wind power industry. Results suggest that U.S. census tracts with higher pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 76 publications
(192 reference statements)
0
0
0
Order By: Relevance
“…Several studies have used residential proximity to pollution sources as a metric to evaluate inequities. These studies have found racial/ethnic and socioeconomic disparities in the spatial distribution of industrial facilities 6,13 , landfills, hazardous waste sites 14,15 , gas 16 and coal-fired power plants 17 , roadways 18 , and other pollution sources 19,20 . Residential proximity studies are generally cross-sectional and often focus on a single air pollution source sector.…”
mentioning
confidence: 99%
“…Several studies have used residential proximity to pollution sources as a metric to evaluate inequities. These studies have found racial/ethnic and socioeconomic disparities in the spatial distribution of industrial facilities 6,13 , landfills, hazardous waste sites 14,15 , gas 16 and coal-fired power plants 17 , roadways 18 , and other pollution sources 19,20 . Residential proximity studies are generally cross-sectional and often focus on a single air pollution source sector.…”
mentioning
confidence: 99%